Evaluation of Eco-physiological Variations on Wheat Productivity under Varying Densities of Ceiba pentandra (L.) Gaertn - Singh, U.S.; Naugraiya, M.N.; Sahoo, M. L.; Puri, S. (Indian Journal of Agroforestry, 2020)
A field study was done on three year old Ceibe pentandra trees planted at 4m x 4m, 4m x 6m and 4m x 8m spacing in a randomized block design. A significant impact of different spacing and distances from the tree base were noticed as regard to yield parameters and yield of wheat. Maximum grain yield of wheat was recorded under 4m x 8m spacing and at central position from the tree base. The increase in yield of crop under lower tree densities and higher distances was found to be associated with maximum PAR availability and least inter and intra specific competition. Photo-synthetically active radiation (PAR) was found maximum in crop growing under wider spacing 4m x 8m and at central position during all the five observation of the day. Further it was found that the availability of PAR differed significantly at 0800 hrs, 1000 hrs, 1200 hrs, 1400 hrs and 1600 hrs for the crop growing under different tree spacing and crop distance. However, the relative humidity showed a decreasing trend with the passage of the time of the day reaching lowest values for all spacing and distances treatment at 1200 hrs. The rise in leaf temperature might be ascribed to rise in ambient temperature with the advancing time of the day.